Blood diamond - DiCaprio, Leonardo; Hounsou, Djimon, 1964-; Connelly, Jennifer; Sheen, Michael; Vosloo, Arnold; Zwick, Edward; Leavitt, Charles; Mitchell, C. Gaby.; Warner Bros. Pictures (1969- ); Virtual Studios (Firm); Spring Creek Productions; Bedford Falls Company; et al. (Burbank, CA : Warner Home Video, 2007)
Danny Archer is an ex-mercenary turned smuggler. Solomon Vandy is a local Mende fisherman. Amid the explosive civil war overtaking 1999 Sierra Leone, these men join together for two dangerous missions: recovering a rare pink diamond of immense value and rescuing the fisherman's son.
Special features: commentary by director Edward Zwick; theatrical trailer.
Originally released as a motion picture in 2006.
Director of photography, Eduardo Serra ; edited by, Steven Rosenblum ; music by, James Newton Howard ; costume designer, Ngila Dickson ; production designer, Dan Weil ; special effects supervisor, Neil Corbould ; visual effects supervisor, Jeffrey A. Okun.
Leonardo DiCaprio, Djimon Hounsou, Jennifer Connelly, Michael Sheen, Arnold Vosloo.
MPAA rating: R; for strong violence and language.
DVD.
Keywords: Diamonds -- Sierra Leone -- Drama; Smugglers -- Sierra Leone -- Drama; Fishers -- Sierra Leone -- Drama; Sierra Leone -- History -- Civil War, 1991- -- Drama; Thrillers (Motion pictures, television, etc.); Action and adventure films; Feature films; War films